PERBANDINGAN KEANEKARAGAMAN BURUNG DI PANTAI SIUNG DAN PANTAI WEDI OMBO GUNUNGKIDUL D.I. YOGYAKARTA - Muhamad Mustafid Amna; Najda Rifqiyati (Universitas Sebelas Maret, 2014)
Abstract- Currently about 50% of birds known in the world are threatened with extinction because of declining quality and loss of habitat. Hunting of wild animals also affect the extinction of birds. Generally, the loss of a habitat is affected by human activities for various reasons, such as land clearing and felling of trees to meet human needs. This happens in some Gunungkidul beach, especially Siung and Wedi Ombo Beach.This research had done on June-July 2013. Observation was using point count method by following the existing lines. In this method the observer walking along the lane / road accompanied with a predetermined observation points is 10 points. At each point, the observations made during the 15-minute observation distance to the left and right as far as ± 25 meters and the distance between a point 200 meters.Based on the research that has been done, in the region Siung Beach recorded 24 families consisting of 44 species of birds. Wedi Ombo Beach recorded 19 families consisting of 33 species of birds. The results of the analysis of bird species diversity index in Siung indicated high diversity, the spread of the number of individuals of each type of high or very wide, and the stability of high community value diversity index 3.074. While Wedi Ombo Beach, indicated moderate diversity, the number of individuals of each type of deployment being and stability of the community with the value of diversity index was 2.584. Keywords: Bird Biodiversity, Gunungkidul, Karst, Siung Beach, Wedi Ombo Beach